ICP22/IE63 Mediated Transcriptional Regulation and Immune Evasion: Two Important Survival Strategies for Alphaherpesviruses - He, Qing; Wu, Ying; Wang, Mingshu; Chen, Shun; Jia, Renyong; Yang, Qiao; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Zhang, Shaqiu; Huang, Juan; Ou, Xumin; et al. (Frontiers in Immunology, 2021)
In the process of infecting the host, alphaherpesviruses have derived a series of adaptation and survival strategies, such as latent infection, autophagy and immune evasion, to survive in the host environment. Infected cell protein 22 (ICP22) or its homologue immediate early protein 63 (IE63) is a posttranslationally modified multifunctional viral regulatory protein encoded by all alphaherpesviruses. In addition to playing an important role in the efficient use of host cell RNA polymerase II, it also plays an important role in the defense process of the virus overcoming the host immune system. These two effects of ICP22/IE63 are important survival strategies for alphaherpesviruses. In this review, we summarize the complex mechanism by which the ICP22 protein regulates the transcription of alphaherpesviruses and their host genes and the mechanism by which ICP22/IE63 participates in immune escape. Reviewing these mechanisms will also help us understand the pathogenesis of alphaherpesvirus infections and provide new strategies to combat these viral infections.